2017
DOI: 10.1111/ijac.12695
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication, characterization, and performance of YbDSB ternary compounds for ITSOFC applications

Abstract: (Yb2O3)x(Dy2O3)y(Bi2O3)1−x−y (0.04≤x+y≤0.20) powders (xYbyDSB) were synthesized by modified sol‐gel Pecchini method. The powders were characterized for structural, surface morphological, thermal, and electrical properties and power density measurements by means of X‐ray diffraction (XRD), scanning electron microscopy (SEM), differential thermal analysis/thermal gravimetry (DTA/TG), and impedance spectroscopy, respectively. Lattice parameters and crystalline size of δ‐phase of Yb2O3‐ and Dy2O3‐doped Bi2O3 sampl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…In a separate study, a cathode-supported electrochemical cell with 6Yb6DSB showed a maximum power density of 72.50 mW/cm 2 at 700 °C . REOs are also used as the electrode material to increase metal oxide fuel cell performance.…”
Section: Applications and Prospects Of Rare Earth Oxidesmentioning
confidence: 98%
See 2 more Smart Citations
“…In a separate study, a cathode-supported electrochemical cell with 6Yb6DSB showed a maximum power density of 72.50 mW/cm 2 at 700 °C . REOs are also used as the electrode material to increase metal oxide fuel cell performance.…”
Section: Applications and Prospects Of Rare Earth Oxidesmentioning
confidence: 98%
“…Eventually, the Yb 3+ content was proven to be a property controller of a ternary system, i.e., (Yb 2 O 3 ) y –(Sc 2 O 3 ) (0.11‑ y ) –(ZrO 2 ) 0.89 ( y = 0–0.11) . Another ternary system, (Yb 2 O 3 ) x (Dy 2 O 3 ) y (Bi 2 O 3 ) 1‑ x ‑ y , also showed high electrical conductivity (i.e., 0.954 S cm –1 ) for 6% mol Yb 2 O 3 and 6% mol Dy 2 O 3 at 800 °C Figure shows the various luminescence parameters (such as absorbance, PL intensity, conductivity, and so on) of the unique Nd 3+ and Dy 3+ -codoped cerium oxide electrolyte compositions for the SOFC.…”
Section: Applications and Prospects Of Rare Earth Oxidesmentioning
confidence: 99%
See 1 more Smart Citation
“…49−52 Stabilization of δ-Bi 2 O 3 to room temperature can be achieved by doping, 53 in mind that incorporation of dopants into the crystal lattice of bismuth(III) influences the physical properties and, for example, reduces the oxygen ion conductivity by several orders of magnitude. 10,54−56 In the last decades, numerous reports have dealt with the stabilization of δ-Bi 2 O 3 using a variety of main-group elements and transition metals (B, 14 P, 57 Ti, 58,59 V, 31−34 Fe, 60 Y, 61,62 Nb, 62,63 Te, 64 Ta, 65 Ce, 66−68 Eu, 69 Tb, 70 Dy, 71,72 Er, 73−75 Tm, 76 Yb, 77,78 Lu, 79 and Th 80 ) and double-doping (Hf/Zr, 81 Te/V, 82 Y/Yb, 83 Er/Nb, 84 Er/Gd, 85 Ho/Gd, 86 Ho/Dy, 87 Dy/W, 88 Sm/Ce, 89 Sm/Yb, 90 La/Mo, 91 Pr/Mo, 92 Dy/Tm, 93 Gd/Lu, 94,95 Yb/Dy, 96,97 Eu, or Tb/Th 98 ).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, a plethora of synthetic approaches for δ-Bi 2 O 3 in the form of powders, ,,,, films, , nanosheets, and nanowires was developed. However, stabilization of pure δ-Bi 2 O 3 at room temperature is still a challenge; therefore, the application of the metastable modification is restricted to a low number of examples. Stabilization of δ-Bi 2 O 3 to room temperature can be achieved by doping, but it must be kept in mind that incorporation of dopants into the crystal lattice of bismuth­(III) influences the physical properties and, for example, reduces the oxygen ion conductivity by several orders of magnitude. , In the last decades, numerous reports have dealt with the stabilization of δ-Bi 2 O 3 using a variety of main-group elements and transition metals (B, P, Ti, , V, Fe, Y, , Nb, , Te, Ta, Ce, Eu, Tb, Dy, , Er, Tm, Yb, , Lu, and Th) and double-doping (Hf/Zr, Te/V, Y/Yb, Er/Nb, Er/Gd, Ho/Gd, Ho/Dy, Dy/W, Sm/Ce, Sm/Yb, La/Mo, Pr/Mo, Dy/Tm, Gd/Lu, , Yb/Dy, , Eu, or Tb/Th…”
Section: Introductionmentioning
confidence: 99%